Rak v Sloveniji - incidenca, ozdravljivost, posledice - Zakotnik, Branko (Rehabilitacija (Ljubljana), 2008)
At the present, about 60.000 inhabitants of Slovenia are cancer patients, most of them cured, some receiving treatment. Their number has been growing each year, partially on the account of higher incidence and partially on the account of more successful treatment. After successful treatment, which is not always without consequences, it is of utmost importance that highly professional physical, psychosocial and professional rehabilitation takes place. Only in the case of successful rehabilitation one can speak of successful treatment. The present article reports the burden of cancer in Slovenia, the success of treatment of some types of cancer and the expected consequences of treatment. Data are shown for 5 most frequent types of cancer - cancer of the lung, breast, colon and rectum, prostate and gynecological cancer that represent more than a half of cancer incidence. Apart from those, the article presents some rare types of cancer such as sarcomas, hematological malignancies, and brain tumors, where rehabilitation plays an important role.
Keywords: posledice; preživetje; rak (medicina); Slovenija